William Shakespeare’s Hamlet in the Critique of James Joyce, D. H. Lawrence and T. S. Eliot: An Overview - Flefil, Anssam Ali; Saadoon, Saad Abd (جامعة ذي قار - كلية التربية للعلوم الإنسانية, 2015)
This research deals with William Shakespeare’s Hamlet (1602) in the critique of James Joyce (1882- 1941), D. H. Lawrence (1885-1930) and T. S. Eliot (1888-1965). By the word “critique,” it is intended to refer to any writing that criticizes a literary work and gives a critical evaluation. Generally, Hamlet has been widely studied over different periods of time and has received various critical interpretations, varied according to an “Age” or to a “Critic.” Therefore, this work aims at shedding light on the chosen play in the critique of three twentieth century writers; namely, Joyce, Lawrence and Eliot. The reasons behind such a choice of writers are that: (1) All of them are prominent modernists belonging to the first decades of the twentieth century. (2) They are the most known literary figures among their contemporaries. (3) They refer to Hamlet in their literary and critical works. The main focus of this study is on Joyce’s critical episode “Chapter Nine” in his novel Ulysses (1922), Lawrence’s essay “The Theatre” in his travel book Twilight in Italy (1916), and Eliot’s essay “Hamlet and His Problems” in his book The Sacred Wood and other Essays (1920). In addition, there are references to other works of the selected writers that have implied criticism to Shakespeare’s Hamlet such as Joyce’s lectures “Amleto di G. Shakespeare” (1913) and posthumous work Giacomo Joyce (1941) as well as to Lawrence’s poem “When I Read Shakespeare.” The significance of this study is that: (1) It contributes uniquely to the domain of literature, especially the field of criticism by giving an overview of the chosen writers and their criticism of Hamlet. (2) It extends our knowledge about criticism in general, and that of Hamlet in particular; and hence, it opens other facets to look for in other fields of study. The task is designed according to the following sequences: it begins with an introduction that gives a general overview about Hamlet and its being a problematic play to many critics throughout periods of time. It then branches into three sections each deals with one of the selected writers respectively, concentrating on their critical writings and views of Hamlet. Finally, it ends with conclusions that sum up the main findings as well as reflect the similar and different points among the three figures of this study. In similarities, to illustrate, the three selected writers criticize Hamlet in their critical career; their criticism is negative and destructive; they all conclude that Hamlet is not without problems. In differences, to keep on, Joyce’s focus is on biographical and personal aspects of Shakespeare himself; Lawrence puts emphasis on psychological aspects of the character of Hamlet; while Eliot’s criticism mainly deals with historical and structural aspects of the play itself.
يتناول هذا البحث مسرحية هاملت لوليم شكسبير (1602) في الأعمال النقدية لكل من جيمس جويس (1882-1914)، دي اج لورنس (1885-1930) و تي اس اليوت (1888-1965) والمقصود من استعمال كلمة "نقد،" هو الإشارة إلى أي كتابة تنقد عملا أدبيا وتعطي تقييما نقديا عموما، لقد دُرست مسرحية هاملت بشكل واسع طوال فترات مختلفة من الزمن واكتسبت تفسيرات نقدية متعددة تنوعت حسب "عصر" و"ناقد" الدراسة. لذلك، يهدف هذا العمل إلى تسليط الضوء على المسرحية المختارة في الأعمال النقدية لثلاثة من كُتَّاب القرن العشرين وهم جويس، لورنس واليوت. الأسباب التي دعت لمثل هكذا اختيار من الكُتاب هي: (1) جميع هؤلاء الكتاب هم حديثون وبارزون وينتمون إلى العقود الأولى من القرن العشرين (2) هم اكثر كُتَّاب الأدب شهرة بين معاصرينهم (3). أشاروا إلى مسرحية هاملت في أعمالهم الأدبية والنقدية. تركز الدراسة الحالية بشكل أساسي على الجزء النقدي المتمثل بالفصل التاسع من رواية يوليسيز لجويس(1922) ، مقالة "المسرح" في كتاب السفر شفق في إيطاليا (1916) للورنس و مقالة "هاملت ومشاكله" في كتاب الغابة المقدسة ومقالات أخرى (1920) لأليوت . فضلا عن ذلك، توحد إشارات لأعمال أخرى للكُتَّاب المختارين والتي تحمل في طياتها نقد ضمني لمسرحية هاملت مثل محاضرات لجويس والتي تحمل عنوان "هاملت لشكسبير" (1913) والعمل الذي نشر بعد وفاته جيمس جويس (1941) بالإضافة إلى قصيدة لورنس " عندما اقرأ شكسبير." لهذه الدراسة أهمية تتمثل في: (1) تساهم بشكل فريد في نطاق الأدب، خصوصا حقل النقد وذلك بإعطاء نظرة عامة حول الكُتاب المختارين لهذه الدراسة ونقدهم لمسرحية هاملت (2) توسع هذه الدراسة مداركنا حول حقل النقد بشكل عام ونقد مسرحية هلملت بشكل خاص وبذلك تفتح أفاق جديدة للبحث في حقول أخرى من الدراسة. هذا العمل مصمم حسب التسلسلات التالية: انه يبدأ بمقدمة تعطي نظرة عامة حول مسرحية هاملت وكونها ذات إشكاليات لعدد من النقاد طوال فترات من الزمن. ثم يتفرع البحث إلى ثلاثة بنود كل يتناول واحدا من الكُتاب وحسب تسلسلهم في هذا البحث، مركزا على كتاباتهم النقدية و وجهات نظرهم المتعلقة بمسرحية هاملت. وأخيرا ينتهي هذا البحث باستنتاجات تجمع النتائج الأساسية وتعكس النقاط المتشابهة والمختلفة بين الأشخاص الثلاثة المختارين . في تشابهات، للتوضيح، ينقد الكُتاب الثلاثة المختارون مسرحية هاملت في أعمالهم النقدية؛ يكون نقدهم سلبياً ومدمراً ؛ يستنتج جميعهم أن مسرحية هاملت لم تخلُ من المشاكل. في اختلافات، لنستمر في نفس السياق، يكون تركيز جويس على السيرة الذاتية والنواحي الشخصية لشكسبير؛ يؤكد لورنس على النواحي النفسية لشخصية هاملت ؛ بينما يتناول نقد اليوت النواحي التاريخية والتركيبية للمسرحية ذاتها.
Keywords: هاملت -- شكسبير، ويليام -- النقد الأدبى -- جويس، جيمس -- لورنس، دى اج -- اليوت، تى اس